What Parents Think about Giving Nonnutritive Sweeteners to Their Children: A Pilot Study - Allison C. Sylvetsky; Mitchell Greenberg; Xiongce Zhao; Kristina I. Rother (International Journal of Pediatrics)
Objective. To evaluate parental attitudes toward providing foods and beverages with nonnutritive sweeteners (NNS) to their children and to explore parental ability to recognize NNS in packaged foods and beverages. Methods. 120 parents of children ≥ 1 and ≤18 years of age completed brief questionnaires upon entering or exiting a grocery store. Parental attitudes toward NNS were assessed using an interviewer-assisted survey. Parental selection of packaged food and beverages (with and without NNS) was evaluated during a shopping simulation activity. Parental ability to identify products with NNS was tested with a NNS recognition test. Results. Most parents (72%) disagreed with the statement “NNS are safe for my child to consume.” This was not reflected during the shopping simulation activity because about one-quarter of items selected by parents contained NNS. Parents correctly identified only 23% of NNS-containing items presented as foods or beverages which were sweetened with NNS. Conclusions. The negative parental attitudes toward providing NNS to their children raise the question whether parents are willing to replace added sugars with NNS in an effort to reduce their child’s calorie intake. Our findings also suggest that food labeling should be revised in order for consumers to more easily identify NNS in foods and beverages.